Формування мовної політики в незалежній Латвійській республіці: моделі, перспективи розвитку - Бикова, Т.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Анализируется современная языковая политика в независимой Латвийской Республике. Осуществлена периодизация становления и формирования языковой политики Латвии, выделено основные четыре модели языковой политики Латвийской Республики. Очеречены перспективы развития языковой ситуации страны в ближайшие годы. In the article description of development and forming of modern linguistic policy is given in independent Latvian Republic. Taking into account experience of predecessors, an author is do a division into the periods of becoming and forming of linguistic policy of Latvia, basic four models of development and formings of linguistic policy, which modern Latvian Republic passed, are selected. In the end logical conclusions and prospects of development of linguistic political situatsi country are given in the nearest years.